Draft Annual Plan (2002-2003) Volume-II Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2002)
The Scheme envisages to provide financial assistance and Infra-structure to the Panchayati Raj Institutions consisting of 67 Gram Panchayats, & Panchayat Samitis and Zila Parishad in these islands for economic development of the villages in rural areas. As per the 73rd Amendment of Constitutions, 67 Gram Panchayat, 7 Panchayat Samiti and one Zila Parishad were started functioning from October 1995. These Panchayats are not having any source of income baring a few, which are having income from market rent etc. in a limited manner. In order to undertake developmental activities in respect of Culverts, footpath, lighting, Sanitation, etc. the Administration releases Grant-in-aid and Matching grants to the PRIs every year.
Andaman and Nicobar Administration, Planning Department